Influencing the degradation rate of recombinant spider silk in the presence of matrix metalloproteinases - Coekin, Thomas (2021)
Understanding the degradation behaviour of extracellular matrix (ECM) scaffolds is essential for predicting and advancing wound healing. Spider-silk based proteins are one type of biomaterial with the potential to be used as a matrix to improve would healing. In addition to good biocompatibility and low-pyrogenicity, silk-based biomaterials have displayed the capacity for controlled degradation, a characteristic that is investigated in this study.